Phase Field Modeling of Dendritic Growth on Spherical Surfaces - Ortellado, Laureano; Gómez, Leopoldo R. (Frontiers in Materials, 2020)
The spontaneous formation of a crystal phase is one of the most common and beautiful pattern formation mechanism in nature. Different instabilities in the crystal interface may lead to the growth of ramified structures, known as dendritic crystal growth. In this work we use a Phase Field Model and numerical simulations to study 2D dendritic growth on curved surfaces. We show how the degree of ramification of a growing nucleus is modified by the underlying curvature of the substrate .